Scuba Diving Experience and Sustainability: An Assessment of Online Travel Reviews - Naidoo, Peunjodi; Ramseook-Munhurrun, Prabha; Li, Jing (The Gaze: Journal of Tourism and Hospitality, 2018)
Scuba diving is a popular activity in small island destinations which is on the rise. However, it is particularly important to preserve the physical environment for small island developing states due to their unique biodiversity and fragile ecosystems. Scuba diving tourism in island destinations is provided mainly by dive operators who are responsible to deliver the scuba diving experience to tourists. However, despite the importance of sustainability for the tourism industry, it is unclear to which extent the marine environment or green issues are important for consumers. Studies are increasingly suggesting that sustainability is an important feature considered by consumers. However, information is sparse regarding the extent to which sustainability is a key component for customers when evaluating the scuba diving experience. In this study, 3109 text reviews from the Trip Advisor website across all 57 listed diving operators in Mauritius were selected for data analysis. Th e present study uses Leximancer, a text analysis software that conducts unsupervised analysis of natural language texts provided in an electronic format. The Gaze: Journal of Tourism and Hospitality Vol.9 2018 p.43-52